DESIGN, SYNTHESIS, AND CHARACTERIZATION OF THE SOME NOVEL 2‐AMINO-PYRIDINE‐3‐ CARBONITRILE AND 2‐AMINO-4H-PYRAN‐3‐CARBONITRILE DERIVATIVES AGAINST ANTIMICROBIAL ACTIVITY AND ANTIOXIDANT ACTIVITY - LAGU, SURENDRA BABU; PRASAD YEJELLA, RAJENDRA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Investigation, the series of newer 2‐amino-pyridine‐3‐carbonitrile and 2‐amino-4H-pyran‐3‐carbonitrile derivative were synthesized and evaluated antimicrobial activities and antioxidant activity. Methods: Novel synthesized chalcones were further condensation to give 2-amino-3-cyanopyridine and 2-amino-3-cyanopyrans in the presence of malononitrile, pyridine, and ammonia acetate. The product is characterized by conventional and instrumental methods. Pyridine and 4-H-Pyran and their analogs occupy prime position due to their diverse applications. Results: The compounds A3C and B3C exhibited marked zone of inhibition with 30.02±0.02 mm and 29.06±0.01 mm, respectively. Docking studies suggested possible interactions with dihydrofolic reductase 4 with 9.15 and −9.67 kcal/mol, respectively. The IC50 30.28±0.01 exhibited A3C by 2,2-diphenylpicrylhydrazyl methods which is better among the series. The 2-amino-3-cyanopyridine derivatives were found good activity than 2-amino-3-cyanopyrane derivative. Among all synthesized compounds few having potent activity and some are near to the standard. Conclusion: Antimicrobial activity and antioxidant of the newly synthesized pyrans and pyridines derivatives will definitely inspire future researchers for the preparation of new analogs.